Upaya Peningkatan Skill dan Knowledge Operator untuk Handling Defects pada PT. X - Nia Adela Saputra; Herri Christian Palit (Jurnal Titra, 2021)
PT. X is a company that produces cigarette filter products in Indonesia. PT. X always makes continuous improvement so that the products produced are of the best quality to maintain the trust of customers. One of the improvements that will be made by PT. X is to improve operator skills and knowledge, so as to increase operator productivity. A production line is said to be productive if the production target on the machine has been met. If the production target is met, the machine downtime will also be lower. One of the factors that cause downtime is the occurrence of defects. Based on the AR (availability rate) report data that has been collected by PT. Previously, the average time for handling defects on 10 machines for 10 weeks was 123.47 minutes per shift or 41.15% of the average production up-time for each shift. This makes the machine's AR value only at 60-70%. If you look at the KPIs that have been determined by the company, the company's target for the AR value is > 85%. The high average downtime causes production results to often do not reach the target and make the machine AR percentage decrease. The higher the downtime percentage, the less finish good will be generated.